Genetic diversity and population structure analysis of 161 broccoli cultivars based on SNP markers - Jingjing Huang; Yumei Liu; Fengqing Han; Zhiyuan Fang; Limei Yang; Mu Zhuang; Yangyong Zhang; Honghao Lv; Yong Wang; Jialei Ji; Zhansheng Li (Horticultural Plant Journal, 2021)
To better understand the genetic diversity and population structure of broccoli cultivars planted in China, a total of 161 representative broccoli cultivars in the past 25 years were collected and analysed based on single nucleotide polymorphism (SNP) markers. Ten pairs of primers with good polymorphism and high resolution were screened from 315 pairs of SNP primers by 3 broccoli accessions (inbred lines) with different phenotypes and maturity. The 10 pairs of SNP primers were selected, producing 78 alleles. The diversity analysis indicated that the polymorphism information content (PIC) of SNP primer ranged from 0.64 to 0.90. The observed number of alleles (Na) was 2.00, the effective number of alleles (Ne) was 1.11–2.00, the Nei's gene diversity (H) was 0.10–0.50, and Shannon information index (I) was 0.20–0.70 using PopGene32 software. The clustering results showed that the 161 broccoli cultivars could be divided into 4 major subgroups (A, B, C and D), foreign cultivars were all assigned to subgroup A, and domestic cultivars were assigned to 3 subgroups of B, C, and D. This study indicated that some domestic cultivars and foreign cultivars were similar in genetic background, but most domestic cultivars were still different from the Japanese cultivars. When K = 2, the population structure result presented that 161 broccoli cultivars could be divided into 1 simple group (2 groups) and 1 mixed group. When Q ≥ 0.6, 143(88.82%) broccoli cultivars belonged to the simple groups. In simple groups 68 (42.24%) broccoli cultivars of group 1 were derived from Japan, the United States, Switzerland, the Netherlands, China-Taiwan, and China-Mainland; 75 (46.58%) broccoli cultivars belonged to group 2; when Q < 0.6, 18 (11.18%) broccoli cultivars belonged to the mixed groups. This study is helpful to understand the diversity and resolution of broccoli cultivars from worldwide, which is beneficial to plant breeding and materials innovation. And meanwhile, this result is also used for construction of broccoli fingerprint serving for cultivar identification.